2016
DOI: 10.1037/emo0000107
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in right-wing authoritarianism and their relation to emotion recognition.

Abstract: This study examined the correlates of right-wing authoritarianism (RWA) in older adults. Participants were given tasks measuring emotion recognition, executive functions and fluid IQ and questionnaires measuring RWA, perceived threat and social dominance orientation. Study 1 established higher age-related RWA across the age span in more than 2,600 New Zealanders. Studies 2 to 4 found that threat, education, social dominance and age all predicted unique variance in older adults' RWA, but the most consistent pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 67 publications
(84 reference statements)
5
27
2
4
Order By: Relevance
“…The results obtained revealed that authoritarianism is not changed linearly with age. These results somewhat differ from the data obtained in a number of foreign works (in the Belgian, Polish and New Zealand samples), in which authoritarianism and its correlates demonstrate linear growth over the entire age range -from adolescence to old age (Cornelis et al, 2009;Ruffman et al, 2016;Truett, 1993). It can be assumed that the dynamics of age differences obtained in our study may be the result of instability typical for the post-Soviet period.…”
Section: Discussioncontrasting
confidence: 99%
“…The results obtained revealed that authoritarianism is not changed linearly with age. These results somewhat differ from the data obtained in a number of foreign works (in the Belgian, Polish and New Zealand samples), in which authoritarianism and its correlates demonstrate linear growth over the entire age range -from adolescence to old age (Cornelis et al, 2009;Ruffman et al, 2016;Truett, 1993). It can be assumed that the dynamics of age differences obtained in our study may be the result of instability typical for the post-Soviet period.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, the 'Vote Leave' campaign message of 'Take Back Control' would seem well constructed to appeal to voters with more authoritarian attitudes as it may resonate with associated motives such as an intolerance for uncertainty and the need for structure and order (Hetherington & Weiler, 2009; John T. Jost et al, 2003). Further, authoritarianism appears higher in older cohorts, with theories suggesting that older people grew up in times when authoritarian attitudes were more common (Ruffman et al, 2016). As such, we PERSONALITY AND COGNITION IN THE EU REFERENDUM 11 additionally expect to see higher scores for RWA and thus more support for a Leave vote among older generations.…”
Section: Authoritarianismmentioning
confidence: 96%
“…Thus, it is possible that people higher in RWAwho are sensitive to threats to traditional and stable social structurescould experience greater symbolic threat from outgroups. There is considerable evidence for this notion, as greater symbolic threat relates to greater RWA (Mirisola & Russo, 2014;Ruffman et al, 2016) and mediates the relation between RWA and prejudice towards international students, gay men and lesbians when referred to as "homosexuals", and dimensions of islamophobia (Charles-Toussaint & Crowson, 2010;Rios, 2013;Uenal, 2016). With respect to the present thesis, perceived female gamer norms, and beliefs and values that conflict with and threaten those of the male gamer status quo, could reflect a symbolic threat.…”
Section: Perceived Threat and Intergroup Attitudesmentioning
confidence: 62%
“…Power and control over the traditional, male gamer identity that is at risk of becoming gender neutral (or female) could represent the resource that groups are in conflict over, prompting a realistic threat. Realistic threat accounts for a significant amount of the variance in RWA (Ruffman et al, 2016) and fully mediates the relation between RWA and prejudice towards international students in the United States (Charles-Toussaint & Crowson, 2010). It is possible that the notion of outgroups succeeding where ingroups do not can threaten social cohesion of the ingroup and subsequently engender negative outgroup attitudes.…”
Section: Perceived Threat and Intergroup Attitudesmentioning
confidence: 99%